Advances in planar filter design - Hong, Jiasheng (Electromagnetics and Radar Ser., 2019)
The book consists of 12 chapters and presents recent advances in planar filters design. It covers a wide range of different design types, technologies, and applications for wireless, microwave, communications and radar systems. The book is based on the latest development in this area and draws on expertise from academic professionals in the field.